'Anti-sluggish' Ti diffusion in HCP high-entropy alloys: Chemical complexity vs. lattice distortions. (February 2023) - Sen, Sandipan; Zhang, Xi; Rogal, Lukasz; Wilde, Gerhard; Grabowski, Blazej; Divinski, Sergiy V.
Graphical abstract: Abstract: Self-diffusion of Ti in HCP HfTiZr and AlScHfTiZr multi-principal element alloys is measured using the radiotracer technique and applying the 44 Ti isotope. In the temperature interval from 973 K to 1373 K, no systematic deviations from linear Arrhenius temperature dependencies are observed. Alloying equiatomic HfTiZr with Al and Sc enhances Ti diffusion rates and the effect becomes more pronounced with increasing Al content. The Ti diffusivities in the present multi-principal element alloys are found to exceed the values predicted by a simple geometric mean of the Ti diffusion coefficients in the pure metals by orders of magnitude, a phenomenon which we refer to as 'anti-sluggish' diffusion. Lattice distortions are speculated to dominate the relative enhancement of Ti diffusion in these HCP high-entropy alloys, inducing the 'anti-sluggish' behavior. The experimental findings are supported by ab initio-derived mean squared atomic displacements and potential energy fluctuations in these alloys.